Conceptual comprehension of pre-service physics teachers towards 1st law of thermodynamics - Bezen, Sevim; Aykutlu, Işıl; Bayrak, Celal (Journal of Turkish Science Education, 2016)
This research is a qualitative study conducted to determine pre-service physics teachers’ conceptual comprehension of the first law of thermodynamics. In this study, which was conducted with the participation of 25 students, case study pattern was used, and a holistic single case pattern was adopted. Five open-ended questions which include drawings and explanations were used as data collection tool. In order to support the obtained findings, semi-constructed interviews were done with 20% of pre-service physics teachers. As a result of the findings obtained from content analysis, it was seen that pre-service teachers represent energy mostly as object with potential energy, electric energy, and vibration energy; and it was seen that they think of the world as an insulated place and thus think that there is confined transformational energy within it. When findings of the study are taken into consideration, it is believed that the first law of thermodynamics should be explained by drawing examples from daily life.
Keywords: Physics Education; Pre-Service Teachers; First Law of Thermodynamics; Conceptual Comprehension